2005
DOI: 10.1563/0-773.1
|View full text |Cite
|
Sign up to set email alerts
|

Antral Membrane Balloon Elevation

Abstract: Many edentulous posterior maxilla are found to be encumbered by alveolar resorption and increased pneumatization of the sinus. These factors limit the quantity and quality of bone necessary for successful implant placement in these areas. One solution is to use shorter implants, but this often results in an unfavorable crown-root ratio. To create an improved environment in such regions, the classic sinus floor elevation with bone augmentation is a well-accepted technique. However, when the edentulous area is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 12 publications
1
50
0
Order By: Relevance
“…Kfir et al [8] and Soltan and Smiler [20] introduced a minimally invasive method of maxillary sinus membrane elevation with balloon insertion into the hole and inflation after drilling down to the maxillary sinus floor and reported good clinical outcomes with the advantages of a low risk of sinus membrane perforation and short surgery time. Hu et al [21] performed sinus membrane elevation using a water balloon with a balloon inflation volume of 0.67±0.17 mL and an elevation of 10.9±2.06 mm in radiological assessment and reported 2 sinus membrane perforation cases.…”
Section: Discussionmentioning
confidence: 99%
“…Kfir et al [8] and Soltan and Smiler [20] introduced a minimally invasive method of maxillary sinus membrane elevation with balloon insertion into the hole and inflation after drilling down to the maxillary sinus floor and reported good clinical outcomes with the advantages of a low risk of sinus membrane perforation and short surgery time. Hu et al [21] performed sinus membrane elevation using a water balloon with a balloon inflation volume of 0.67±0.17 mL and an elevation of 10.9±2.06 mm in radiological assessment and reported 2 sinus membrane perforation cases.…”
Section: Discussionmentioning
confidence: 99%
“…and reduction of precedure time to approximately 60 minutes operatory time 1, 2, 6-11 . It was found that the maxillary sinus augmentation with balloon systems present minimal postoperative discomfort and pain, resulting in patient comfort and reduction of analgesic use [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…For dental surgeons, obtaining stem cells from dental tissues is a simple and minimally invasive procedure; (DPSCs) are multipotent, possessing high capacity for self-renewal and expansion in vitro, and can differentiate into cells of all germ layers, including ectoderm (nerve cells), mesoderm (myocytes, osteoblasts, chondrocytes , Adipocytes and cardiomyocytes) and endoderm (hepatic cells). Dental pulp stem cells may be ideal candidates for reconstructive therapy as they are devoid of the ethical problems associated with other types of stem ce [66][67][68][69][70][71][72][73][74][75][76][77][78][79] .…”
Section: Stem Cells:-mentioning
confidence: 99%